Alexithymia in Patients With Substance Use Disorders and Its Relationship With Psychiatric Comorbidities and Health-Related Quality of Life - Palma-Álvarez, Raul F.; Ros-Cucurull, Elena; Daigre, Constanza; Perea-Ortueta, Marta; Serrano-Pérez, Pedro; Martínez-Luna, Nieves; Salas-Martínez, Anna; Robles-Martínez, María; Ramos-Quiroga, Josep A.; Roncero, Carlos; Grau-López, Lara (Frontiers in Psychiatry, 2021)
Background: Alexithymia frequently correlates with several psychiatric disorders, including substance use disorder (SUD). However, most studies reporting the associations between alexithymia and psychiatric disorders have been performed in populations without SUD. This research, therefore, evaluates alexithymia in Spanish patients with SUD and the relationship among alexithymia, psychiatric comorbidities, psychological symptoms/traits, SUD variables, and health-related quality of life (HRQoL). Methodology: A cross-sectional study was conducted with 126 Spanish outpatients with SUD (75.4% males; mean age 43.7214.61 years), correlating their alexithymia levels (using the Toronto Alexithymia Scale 20 [TAS-20]) to their psychiatric comorbidities, psychological symptoms/traits, SUD variables, and HRQoL. Results: Alexithymia was significantly higher in patients who had cannabis use disorder. Higher alexithymia scores were also related to higher levels of depression, anxiety, impulsivity, and lower HRQoL. After multivariate analysis, trait anxiety, impulsivity, and the physical component summary of the HRQoL were found to be independently related to alexithymia. Conclusions: SUD patients with higher alexithymia levels have more frequently psychiatric comorbidities, present specific psychological features, and have worse HRQoL. Hence, it is important to evaluate these factors and offer more accurate psychotherapeutic approaches for this patient population.